Desarrollo de un sistema de indicadores de sostenibilidad ambiental para la conservación del cerro Putzalahua en la parroquia de Belisario Quevedo, cantón Latacunga, provincia de Cotopaxi, período 2021-2022. - Gutierrez Toscano, Katy Vanessa (2022)
This research project aims to develop an environmental sustainability indicators system for the conservation of the “Putzalahua” hill in the Belisario Quevedo parish, located in the Latacunga canton, province of Cotopaxi, it is intended to establish an evaluation indicators system of environmental sustainability as a tool for the conservation of the “Putzalahua” hill. The methodology that was applied was based on the deductive-inductive method - supported by bibliographic, theoretical and scientific documentation, allowing to determine the environmental problem and the selection of indicators, in addition to the use of geographic information tools (Qgis). For the characterization of the study area, the information was supplemented by in-situ visits and unstructured interviews that were applied to the authorities of the parish and inhabitants of the surrounding communities through non-probabilistic sampling. For the selection of indicators, the PSR (Pressure-state-response) method was applied: Pressure establishes the human activities that generate changes in the environment; State, is the current situation of the environment and its natural resources and Response, are the actions established by the government or other entities in the face of the identified environmental problem. Thus establishing 30 indicators, in terms of pressure, indicators were identified on introduced flora and fauna, forest fires and deforestation. On the other hand, in terms of status, overgrazing predominates, extinction of flora and fauna species, change in ecosystem functionality in affected areas and decrease in soil quality. While in response, the lack of investment in training in the different sectors stands out. Based on this, methodological files were prepared based on five selected factors: agriculture, water, biodiversity, soil and tourism. For this, strategies and activities focused on strengthening and guiding correct and timely decision-making by social actors involved in conservation and sustainable development for this tourist attraction and its ecosystem were generated.